Utilizing Google Workspace for Teaching English as A Foreign Language - Muhammad Fadli; Valdi Mughni Budiman; Syaifuddin Muhammad Mirza (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The rapid advancements in information and communication technology (ICT) have transformed the education sector, particularly in integrating digital tools into teaching practices. This study explores the utilization of Google Workspace for Education in teaching English as a foreign language at Politeknik Negeri Lampung. Using a qualitative descriptive method, data were collected through semi-structured interviews with five English lecturers. The findings reveal that tools like Google Classroom, Docs, Slides, Meet, and Drive. Enhance teaching efficiency, foster collaboration, and improve student engagement. These tools support diverse teaching learning activities, including material preparation, interactive learning, and formative and summative assessments. Moreover, the accessibility of Google Workspace allows learning to take place anytime and anywhere, aligning with the demands of modern education. This study underscores the importance of lecturers developing ICT skills to leverage digital tools effectively and create innovative learning environments. The integration of Google Workspace significantly contributes to improving the quality of English language teaching learning in the digital era.